2017
DOI: 10.1080/22423982.2017.1320919
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype and response to training during the polar night: a pilot study

Abstract: Background: An individual’s chronotype influences his or her physiological rhythms. Some studies have looked at the effect of time of day on the responses to exercise, but studies on the effect of long-term training are lacking.Objective:  To report the effects of an 8-week training period during the polar night in non-athletes of different chronotypes living at 70°N.Design:  In all, 10 morning (M), 10 neither (N) and 10 evening (E) types were recruited, and their aerobic capacity (VO2max), strength, flexibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…It is crucial, in future longitudinal studies, to control for potential confounding factors, such as competing synchronizers, noncontrolled diet, environmental conditions, exercise characteristics (time of day, mode, intensity and duration), and inter-individual variability with the aim to reduce the methodological bias. With reference to the inter-individual variability, it results essential to highlight that the subjects' chronotype is able to largely influence and affect behavioural, physiological, and bio-psychological characteristics and, consequently, the circadian system in general (Adan et al, 2012;Bonato et al, 2017a;Bonato et al, 2017b;Montaruli et al, 2017;Rossi et al, 2015;Roveda et al, 2017a;Vitale et al, 2013;Vitale et al, 2015;Vitale et al, 2017a;Vitale et al, 2017b;Vitale et al, 2017c;Vitale et al, 2017d). The correct chronobiologic approach to the problem and the standardization of all confounding factors are needed to reach more clear evidence-based results.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial, in future longitudinal studies, to control for potential confounding factors, such as competing synchronizers, noncontrolled diet, environmental conditions, exercise characteristics (time of day, mode, intensity and duration), and inter-individual variability with the aim to reduce the methodological bias. With reference to the inter-individual variability, it results essential to highlight that the subjects' chronotype is able to largely influence and affect behavioural, physiological, and bio-psychological characteristics and, consequently, the circadian system in general (Adan et al, 2012;Bonato et al, 2017a;Bonato et al, 2017b;Montaruli et al, 2017;Rossi et al, 2015;Roveda et al, 2017a;Vitale et al, 2013;Vitale et al, 2015;Vitale et al, 2017a;Vitale et al, 2017b;Vitale et al, 2017c;Vitale et al, 2017d). The correct chronobiologic approach to the problem and the standardization of all confounding factors are needed to reach more clear evidence-based results.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding further reported no significant difference on Vo 2 Max and hematological quantities between I-type and M-type chronotype among students from low altitude living in a tropical setting. However, previous studies reported a better VO 2 max in E-types than M-types [68,7072]. This might be reflective of better aerobic participation in energy metabolism during the evening time, leading to both mental and physical activeness among E-type than other chronotype [16,36,73].…”
Section: Discussionmentioning
confidence: 90%
“…Everyone has a biological or circadian rhythm, determined by various hormones [ 4 ]. Regulates the sleep/wake system and many other features such as blood pressure, hormone levels, body temperature, physical performance, alertness, mood, and intellectual ability to fluctuate during the day [ 5 ].…”
Section: Introductionmentioning
confidence: 99%